Communities' views, attitudes and recommendations on community-based education of undergraduate Health Sciences students in South Africa: A qualitative study - Langalibalele H. Mabuza; Paula Diab; Stephen J. Reid; Busisiwe E. Ntuli; Penelope S. Flack; Ratie Mpofu; Priscilla S. Daniels; Tracy-Ann Adonis; Mandisa Cakwe; Mugambi W. Karuguti; Ngkatiseng Molefe (AOSIS, 2013)
Background: Medical and Health Sciences students in South Africa undertake community-based education (CBE). Health professionals based at host sites are jointly responsible for training of these students in conjunction with university staff. This study explored the communities' views, attitudes and recommendations regarding CBE undertaken by these students, in order to improve the qualityof community support for these programmes. Method: A qualitative descriptive study was conducted at CBE placement sites of students from the Faculties of Health Sciences of the University of Limpopo (UL), University of KwaZulu-Natal (UKZN) and University of the Western Cape (UWC) during 2010 and 2011. Focus group discussions were held with site facilitators, community leaders and patients, and interviews were audio recorded, transcribed and translated into English where necessary. Data were analysed using NVivo (version 9). Findings: CBE was seen to benefit communities, students and host institutions as there was perceived improvement of service delivery, better referral to hospitals and reduction of workloads on site staff.CBE was also seen as having potential for recruiting professionals who have better orientation tothe area, and for motivating school pupils for a career in health sciences. Students acquired practicalskills and gained confidence and experience. Challenges included poor communication between universities and host sites, burden of student teaching on site facilitators, cultural and religious sensitivity of students and language barriers. Conclusion: The study revealed that communities have an important role to play in the CBE offuture health care professionals. CBE activities could be better organised and managed through formalised partnerships.